Monetary Integration - Currency in the Euro Area and Economic Club Theory - Piotr WALĄG (Communications of International Proceedings, 2020)
The article is an attempt by the authors to fit in with the discussion on the benefits and costs of joining the euro area, which focuses primarily on the differences between countries in real structures. The thesis of the article is that full economic and monetary integration will increase costs among those countries whose broadly understood socio-economic structure differs from that of the most developed countries. Differences in GDP or asset structure (especially in periods of falling global demand) inevitably lead to the fact that the rising costs of competition (efforts) will be transferred to societies that generate their income from internationally immobile resources. The theory of clubs will be applied to verify the thesis. Countries integrated in the euro area are identified as members of a club that offers the club good - the common currency. The existence of differences that make the club heterogeneous through costs and benefits will determine the optimal size of the club.
Keywords: club theory; monetary-currency integration; eurozone; asymmetric demand shocks; nominal convergence; real divergence; not internationally mobile assets.